Gastrointestinal bleeding - Dinis-Ribeiro, Mário (Endoscopy, 2013)
GI bleeding remains an important health outcome. A significant number of abstracts were presented during Digestive Disease Week in Orlando, Fla, from May 18 to 21, 2013, noting the global management of patients with GI bleeding and reporting the efficacy of endoscopic interventions for upper or lower GI bleeding, the management after bleeding occurring as a complication of diverse therapeutic interventions in the GI tract. Presented here is a putative summary of the most relevant abstracts.